How are necrotic cells recognized by their predators?. Issue 1 (2nd January 2016) - Li, Zao; Zhou, Zheng
Abstract: Necrosis is a type of cell death often caused by cell injury and is linked to human diseases including neuron degeneration, stroke, and cancer. Cells undergoing necrosis are engulfed and degraded by engulfing cells, their predators. The mechanisms by which necrotic cells are recognized and removed remain elusive. Here we comment on our recent findings that reveal new molecular mechanisms of necrotic-cell recognition. Through studying the C. elegans touch neurons undergoing excitotoxic necrosis, we identified a receptor/ligand pair that enables engulfing cells to recognize necrotic neurons. The phagocytic receptor CED-1 is activated through interaction with its ligand phosphatidylserine (PS), exposed on the surface of necrotic cells. Furthermore, against the common belief that necrotic cells have ruptured plasma membrane, we found that necrotic C. elegans touch neurons actively present PS on their outer surfaces while maintaining plasma membrane integrity. We further identified 2 mechanisms governing the presentation of PS, one of which is shared with cells undergoing apoptosis, a "cell suicide" event, whereas the other is unique to necrotic neurons. The influx of Ca 2+, a key necrosis-triggering factor, is implicated in activating a neuronal PS-scramblase for PS exposure. We propose that the mechanisms controlling PS-exposure and necrotic-cell recognition by engulfing cells are likely conserved from worms to humans.